Multi-layer flexible packaging with anti-oxidant properties

A multilayer flexible package with a core-shell antioxidant structure addresses the limitations of existing methods by ensuring uniform distribution and protection, enhancing antioxidant stability and activity, thus improving the shelf life of air-sensitive materials.

JP7602012B2Active Publication Date: 2024-12-17SAES GETTERS SPA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023506024
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-30
Filing Date
2021-07-29
Publication Date
2024-12-17
Estimated Expiration
2041-07-29

AI Technical Summary

Technical Problem

Existing methods for integrating antioxidants into packaging systems face limitations such as reduced antioxidant activity with distance from the outer portion, damage from high temperatures during extrusion, and instability under oxygen, light, pH, and storage time, limiting their effectiveness and application thickness.

Method used

A multilayer flexible package with a core-shell structure is developed, comprising an antioxidant core with a particle size of 0.1 to 10 μm and a polymer shell covering at least 70% of the core, dispersed in a polymer coating, which includes antioxidant capsules with a reduction potential of 0.1 to 0.5 V.

Benefits of technology

The core-shell structure ensures uniform distribution and protection of antioxidants, enhancing their stability and activity, preventing decomposition and extending the shelf life of air-sensitive materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602012000002
    Figure 0007602012000002
  • Figure 0007602012000003
    Figure 0007602012000003
  • Figure 0007602012000004
    Figure 0007602012000004
Patent Text Reader

Abstract

The multilayer flexible package comprises a polymer coating (2) containing a dispersion of antioxidant capsules (3) having a core-shell structure comprising antioxidant cores (4) having a particle size distribution comprised between 0.1 and 10 μm and a reduction potential comprised between 0.1 and 0.5 V, and a polymer shell (5) covering at least 70% of the cores (4).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to multi-layer flexible packages characterized by the antioxidant properties available in core-shell based dispersions. [Background technology]

[0002] In the field of packaging and storage of air-sensitive materials, one of the most important goals to be achieved is to avoid the loss of material properties due to oxidation-related degradation. For example, oxidation processes are considered the main cause of deterioration of perishable products and foods, affecting their quality and safety, especially the nutritional and sensory qualities of foods.

[0003] One possible solution to this problem relies on the use of antioxidant species that can inhibit oxidation reactions and the subsequent production of free radicals.

[0004] In this field, the integration of said antioxidants into effective packaging is one of the most promising alternatives for the control of oxidation-related decomposition processes.

[0005] The method mainly used discloses the incorporation of antioxidant molecules, in particular catechin, into the polyurethane matrix by adding them to one of the components of the polyurethane adhesive before the polymerization reaction or after mixing of the two reagents of the composition, for example representing the addition of antioxidant species during the polymerization process as reported in WO 2014 / 170426.

[0006] US2006 / 0047069 also applies a similar strategy of adding antioxidants to polymer dispersions during the polymerization process, setting a specific pH range.

[0007] Another possible method is reported in WO2017 / 049364, which discloses a food packaging material comprising a polymeric material and a natural antioxidant. The disclosed method for obtaining the packaging material involves the addition of a natural antioxidant as a solid, liquid, oil, powder or emulsion to a polymeric material, followed by a process of extrusion (including cast film extrusion and blown film), molding or lamination to form the food packaging material.

[0008] Yet another method for adding antioxidants to polymeric materials is disclosed in GB 2237574, which shows the preparation of capsules by spraying an emulsion of antioxidant and aqueous sodium alginate into a crosslinking bath containing an aqueous solution of a di- or polyvalent metal salt. The instantaneous reaction between the emulsion and the metal causes the alginate to crosslink and form a "sponge"-like matrix containing the antioxidant in its interstices. Although the matrix particles are referred to as capsules and the process as encapsulation in the text, this terminology should not be construed as including "balloon" type capsules having distinct boundary walls, but rather the capsules disclosed in GB 2237574 are "sponge"-like with irregular surfaces and numerous pores. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] WO2014 / 170426 [Patent Document 2] US2006 / 0047069 [Patent Document 3] WO2017 / 049364 [Patent Document 4] GB2237574 Summary of the Invention [Problem to be solved by the invention]

[0010] However, the disclosed method presents some critical points for end use in packaging systems, such as the layer thickness that can be finally reached is essentially never less than 100-200 μm, with the result that the possible applications of the final solution are reduced. Further layering is represented by the placement of antioxidant species in the layers of the package, with the result that the antioxidant activity is reduced depending on the distance from the outer part of the container. Furthermore, the integration of some specific molecules, such as catechins, and their distribution are strictly related to their chemical compatibility with the properties of the polymer used.

[0011] Further drawbacks relate to the application, for example, during the extrusion process at elevated temperatures, which can lead to damage of the antioxidant molecules. Indeed, it is important to point out that the use of antioxidants in this field is limited by their own properties, in particular their instability under exposure to oxygen, light, high temperature, pH and storage time. [Means for solving the problem]

[0012] The object of the present invention is to produce a multi-layer flexible package which overcomes the above mentioned drawbacks. This object is achieved by a multi-layer flexible package comprising at least one polymer coating containing a dispersion of antioxidant capsules having a core-shell structure comprising an antioxidant core with a particle size distribution comprised between 0.1 and 10 μm and a reduction potential comprised between 0.1 and 0.5 V, and a polymer shell covering at least 70% of the core. [Brief description of the drawings]

[0013] The structure and properties of the package according to the present invention will become apparent to those skilled in the art from the following detailed description of several embodiments and the accompanying drawings: [Figure 1] FIG. 2 is a schematic cross-sectional view of a film used in a first embodiment of the present invention. [Diagram 2] FIG. 2 is a view similar to FIG. 1 of a film used in a second embodiment of the invention. [Figure 3A]1 is a graph comparing the oxidation delay provided by an embodiment of a capsule according to the present invention to three other solutions outside the scope of the present invention. [Figure 3B] 1 is a graph comparing the oxidation delay provided by an embodiment of the present invention versus two other solutions outside the scope of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] For the purposes of the present invention, the above particle distribution range means that 90% of the dispersed capsules have an average volume diameter that falls within the claimed range, as measured by laser diffraction. Definitions and discussion of the theory and practice of laser diffraction are derived from the ISO13320:2020 standard. It has been found that the reduction potential of an antioxidant species is related to the ease with which a compound can donate hydrogen to free radicals, and the lower the reduction potential, the higher the antioxidant's hydrogen-donating ability. Thus, antioxidant species with reduction potentials comprised between 0.1 and 0.5 V have been proven to be the most effective in carrying out their antioxidant effect of avoiding the degradation of air-sensitive materials contained within the package.

[0015] In particular, the antioxidant species used in the present invention are selected from the group consisting of tannic acid, propyl gallate, gallic acid, caffeic acid, ascorbic acid and ferulic acid.

[0016] It was found that particle size is an important parameter for reducing the reduction potential of antioxidant materials, with a large effect from particle size 100 μm to 10 μm. Furthermore, particle size and shape are important properties that allow the integration of antioxidants in packaging structures. In particular, packaging systems for food, cosmetics, dietary supplements and pharmaceuticals typically consist of layers with a thickness in the range of 0.5-100 μm, where the particles with a size comprised between 0.1-10 μm and spherical shape can ensure a fine distribution of functional fillers, e.g. antioxidant particles.

[0017] The preparation of antioxidant particles having a size of 0.1-10 μm according to the present invention is not made by mechanical processes typically used for the preparation of powders (as a result of which it is difficult to obtain powders with a particle size of less than 100 μm), but by intermediate steps involving solubilization of the material and subsequent precipitation, either wet or dry. Such processes can be solvent evaporation, sol-gel methods, microemulsions, layer-by-layer adsorption techniques, macroemulsification, membrane-assisted emulsification, membrane-assisted nanoprecipitation, in situ polymerization, droplet formation / phase separation, interfacial polymerization, prilling, spray drying, freeze drying, ionic gelation or fluidized bed techniques.

[0018] A capsule system is achieved by the presence of a polymer shell covering an antioxidant core, the polymer being added in an amount such that the ratio of the mass of the shell to the mass of the total core-shell system is comprised between 0.25 and 0.75. In this way, each capsule 3 has a core-shell structure comprising an antioxidant core 4 with a reduction potential comprised between 0.1 and 0.5 V, and a polymer shell 5 covering the core 4.

[0019] The polymer shell 5, in a first embodiment of the invention, may be selected from sugars, gums, lipids, proteins, natural polymers, fossil-derived polymers and copolymers thereof, in a preferred form the natural polymers are alginates and the fossil-derived polymers and copolymers thereof are polyethylene-co-(vinyl alcohol) (EVOH).

[0020] Furthermore, said polymer shell 5 covers at least 70% of the core 4, and in a preferred embodiment covers the core 4 completely.

[0021] In alternative embodiments, the polymer shell 5 may be glutaraldehyde, diphenylphosphoryl azide (DPPA), genipin, or enzymes such as transglutaminase, tyrosinase, and laccase.

[0022] The capsules 3 are dispersed in the polymer coating 2 in an amount of 5 to 50% by mass relative to the polymer coating 2.

[0023] Said polymer coating 2 is characterized by a thickness comprised between 0.5 and 100 μm and may be selected from acrylics, acrylic-styrene, -vinyl and alkyd copolymers, urethane-acrylics, aliphatic-urethanes, urethanes, polyesters, biopolyesters, epoxies, siloxanes and polysiloxanes, polyurethanes, polystyrenes, phenolics, poly(ethylene-co-vinyl alcohol) (EVOH), poly(vinyl alcohol) (PVAL), poly(lactic-co-glycolic acid) (PLGA), polyethylene glycol (PEG), polyethylene (PE), polystyrene (PS) and their copolymers, poly(vinyl acetate) (PVAC), water-based and water-reducible latexes.

[0024] In this regard, the use of an antioxidant system based on core-shell technology (capsules), as described in the present invention, is sufficient to prevent the degradation of the antioxidants, improve the protection and integration of the active materials in the final structure and increase the control of their functional activity, without the need for additional protective components.

[0025] In addition, a further relevant property to be considered in the integration of antioxidants into an effective package relates to the dispersion of said materials in the organic matrix. More specifically, the use of core-shell structures, unlike the powder systems mainly reported in the prior art, allows for increased control and uniformity of the dispersion, resulting in improved performance.

[0026] Therefore, taking into account the complexity of the overall system, the core-shell capsules of the present invention can be prepared in different steps, as described above, avoiding the degradation of the antioxidants and at the same time allowing a uniform and regular distribution of said capsules in the polymer matrix.

[0027] To improve some specific properties of the package, filler materials may further be added to the polymer coating 2 in an amount comprised between 1 and 30% by weight with respect to the polymer coating 2. Said fillers may be selected from zeolites, hydrotalcites, zirconium phosphates, porphyrins, graphene and other two-dimensional crystals, graphene oxide, metal organic frameworks (MOFs), cellulose and capsules of ethylene-vinyl alcohol copolymers.

[0028] For example, if a moisture barrier effect is to be achieved, the filler may be a zeolite selected from faujasite (FAU), mordenite (MOR), ZSM-5 and Linde Type A. Furthermore, in a further embodiment, it is possible to have an oxygen barrier effect with the addition of a dispersion of a first ethylene-vinyl alcohol copolymer in particulate form with an ethylene content comprised between 24 and 38 mol% (high ethylene content) and a second ethylene-vinyl alcohol copolymer with an ethylene content of less than 15 mol% (low ethylene content), as reported for the capsules described in WO2020 / 012396 filed in the name of the applicant.

[0029] In a preferred embodiment, the polymer coating 2 is applied as a continuous frame around the perimeter of the package or as a continuous layer covering the entire surface of the package.

[0030] As shown in FIG. 1, the polymer coating 2 containing the core-shell capsules 3 can be used to bond to several types of substrates 1, such as polypropylene (PP), oriented polypropylene (OPP), biaxially oriented polypropylene (BOPP), polyethylene (PE) and low density polyethylene (LDPE), polyamide (PA) and biaxially oriented polyamide (BOPA), polyethylene terephthalate (PWT) and biaxially oriented polyethylene terephthalate (BOPET), polyethylene furanoate (PEF), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), polylactic acid (PLA), biaxially oriented polylactic acid (PLA), mater-bi (corn starch based biodegradable plastic), polyhydroxyalkanoates (PHAs), starch blends, paper and laminated paper, lignocellulose blends, and cellophane.

[0031] Furthermore, the polymer coating 2 may be covered with a polymer layer 6 selected from polyethylene (PE), machine direction oriented polyethylene (MDO-PE), low density polyethylene (LDPE), acrylics, acrylic-styrene, acrylic copolymers, siloxanes and polysiloxanes, as shown in FIG. 2.

[0032] Finally, considering the broad interest in the preservation of different air-sensitive materials, the solutions described herein can be easily adopted in food, cosmetic, dietary supplement or pharmaceutical packaging systems. EXAMPLES

[0033] The invention can now be described in more detail with reference to the following examples.

[0034] Preparation of sample S1 according to the present invention The core-shell capsule 3 was prepared by adding 1% by weight of chitosan, as a precursor of the polymer shell 5, to a 0.1 M HCl solution kept at room temperature under stirring at 200 rpm. After solubilization, tannic acid, as an antioxidant material, was added at 2% by weight to the chitosan solution, and stirring was maintained under the same conditions. After solubilization, the resulting formulation was spray-dried to obtain the core-shell capsule 3, in which at least 90% of the particles are present in the form of monodisperse capsules with a particle size (diameter) of less than 10 μm.

[0035] Preparation of Comparative Sample C1 The antioxidant particles without shell were prepared by adding tannic acid at 4% by weight to an aqueous solution kept at room temperature under stirring at 200 rpm. After its solubilization, the resulting formulation was spray-dried to obtain particles present in the form of monodisperse particles, at least 90% of which have a particle size (diameter) of less than 10 μm.

[0036] Table 1 below reports the spray drying parameters employed during sample preparation:

[0037] [Table 1]

[0038] Description of comparative sample C2 Tannic acid purchased from Sigma Aldrich was selected as a comparative sample without subjecting it to a step of conversion into particles. Sample C2 was present in the form of a powder with at least 90% of the particles having a particle size (diameter) of less than 100 μm.

[0039] Coating preparation According to the present invention, the above samples S1, C1 and C2 were then dispersed in two different polymer matrices in order to obtain low thickness coatings.

[0040] A) Samples S1, C1 and C2 were dispersed in a polyethylene glycol dimethacrylate solvent-free polymer resin containing 1% of a hydroxyketone-based system as a photoinitiator in an amount of 10% by weight relative to the polymer coating. For the preparation of polymer coatings characterized by low film thickness values, the resulting dispersions were bladed onto PET using a spiral bar with a nominal thickness of 4 μm, and the resulting coatings were subjected to a UV curing process (15 s, 100 mW / cm2). 2 ) Sample S1 was characterized by a more regular and uniform distribution of capsules in the polymer layer than sample C2, whose size could not guarantee a regular distribution of the antioxidant material in the low thickness polymer layer. When comparing samples S1 and C1, the presence of the polymer shell protected the reactivity of the antioxidant to the polymer binder and ensured its uniform distribution and functionality.

[0041] B) Samples S1, C1 and C2 were dispersed in a polysiloxane solvent-free polymer resin in an amount of 10% by weight relative to the polymer coating. For the preparation of polymer coatings characterized by low film thickness values, the resulting dispersions were applied with a spiral bar with a nominal thickness of 4 μm on PET and the resulting coatings were subjected to a thermal curing step at 80° C. for 45 minutes. Sample S1 was characterized by a more regular and homogeneous distribution of capsules in the polymer layer than sample C2, whose size does not allow to guarantee a regular distribution of antioxidant material in the low film thickness polymer layer. When comparing samples S1 and C1, the presence of the polymer shell protected the reactivity of the antioxidant towards reactive species, as explained in the following paragraphs.

[0042] Particle functionality by microcalorimetry The antioxidant capacity of samples S1, C1 and C2 was tested by microcalorimetry to measure the inhibition of oxidation reactions, compared to linseed oil (LO) alone as a standard reference and LO mixed with samples S1, C1 and C2. In constant temperature mode, the oil in a thermostat was maintained at a temperature of 30°C and the heat produced was continuously measured over time.

[0043] The graph in Figure 3A shows the results of the activity of samples S1, C1 and C2 in comparison with the delay in terms of oxidation of standard linseed oil (LO). It is clear that sample S1 ensured a significantly longer protection time in terms of oxidation of linseed oil compared to the particles of sample C1 and the powder of sample C2. In particular, for sample C2 in powder form with a particle size (diameter) of less than 100 μm, no relevant antioxidant capacity was observed under the test conditions.

[0044] Functionality of coatings by microcalorimetry. The antioxidant capacity of the coatings containing samples S1 and C1 was tested by microcalorimetry to measure the inhibition of oxidation reactions, comparing linseed oil (LO) alone as a standard reference and LO mixed with the coatings containing samples S1 and C1. In constant temperature mode, the oil in the thermostat was maintained at a temperature of 30° C. and the heat generated was continuously measured over time.

[0045] The graph in Figure 3B shows the results of the activity of samples S1 and C1 compared to the retardation in terms of oxidation of standard linseed oil (LO). Each coating was prepared by method A, i.e., dispersing the sample in a polyethylene glycol dimethacrylate solvent-free polymer resin.

[0046] It was therefore demonstrated that the coating containing sample S1 ensured protection of the linseed oil in terms of oxidation for more than 20 hours, whereas the use of the coating containing sample C1, due to the absence of a protective shell, led to an immediate reaction of the antioxidant particles, resulting in a shortened shelf life. [Explanation of symbols]

[0047] 1...Base material 2. Polymer Coating 3 capsules 4. Core 5. Polymer shell 6 Polymer layer

Claims

1. 1. A multi-layer flexible package comprising at least one polymeric coating comprising a dispersion of antioxidant particles, the antioxidant particles are contained in capsules having a volume average diameter comprised between 0.1 and 10 μm, an antioxidant core having a reduction potential comprised between −0.1 and 0.5 V; and - a polymeric shell that covers at least 70% of said core A multi-layer flexible package having a core-shell structure comprising:

2. 10. The package of claim 1, wherein the antioxidant is selected from the group consisting of tannic acid, propyl gallate, gallic acid, caffeic acid, ascorbic acid, and ferulic acid.

3. 10. The package of claim 1, wherein the polymer shell is selected from the group consisting of sugars, gums, lipids, proteins, natural polymers, fossil derived polymers, and copolymers thereof.

4. 2. The package of claim 1, wherein the polymeric coating is selected from the group consisting of acrylics, acrylic-styrene, vinyl-alkyd copolymers, urethane-acrylics, aliphatic-urethanes, urethanes, polyesters, bio-polyesters, epoxies, siloxanes, polysiloxanes, polyurethanes, phenolics, polyethylene-co-(vinyl alcohol) (EVOH), poly(vinyl alcohol) (PVAL), poly(lactic-co-glycolic acid) (PLGA), polyethylene glycol (PEG), polyethylene (PE), polystyrene (PS) and copolymers thereof, poly(vinyl acetate) (PVAC), water-based and water-reducible latexes.

5. The package according to claim 1, wherein the polymer coating has a thickness comprised between 0.5 and 100 μm.

6. The package according to claim 1, wherein the antioxidant capsules are added to the polymer coating in an amount comprised between 5 and 50% by weight.

7. 2. The package according to claim 1, wherein the ratio between the mass of the shell and the total mass of the core-shell system is comprised between 0.25 and 0.

75.

8. The package of claim 1, wherein the polymeric coating further comprises a filler in an amount comprised between 1 and 30% by weight of the polymeric coating.

9. 10. The package of claim 1, wherein the polymeric coating is associated with a substrate selected from the group consisting of polypropylene (PP), oriented polypropylene (OPP), biaxially oriented polypropylene (BOPP), polyethylene (PE), low density polyethylene (LDPE), polyamide (PA), biaxially oriented polyamide (BOPA), polyethylene terephthalate (PET), biaxially oriented polyethylene terephthalate (BOPET), polyethylene furanoate (PEF), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), polylactic acid (PLA), bio-oriented polylactic acid (PLA), polyhydroxyalkanoate (PHA), starch mixtures, paper, laminated paper, lignocellulose mixtures, and cellophane.

10. 2. The package of claim 1, wherein the polymeric coating is covered with a polymer layer selected from the group consisting of polyethylene, machine direction oriented polyethylene (MDO-PE), low density polyethylene (LDPE), acrylic, acrylic-styrene, acrylic copolymers, siloxanes, and polysiloxanes.

Citation Information

Patent Citations

  • Method of encapsulating polymer additives

    GB2237574A

  • Novel applications for oxygen-capturing compositions

    JP2001514131A

  • antioxidant active food packaging

    JP2018537369A

  • Polymer dispersions having improved polyene-fungicide tolerance, their production and use for food coating

    US20060047069A1

  • Multilayer assembly

    WO2014170426A1